A SPOKE IN THE WHEEL: A NOVEL ABOUT THE BUDDHA BY AMITA KANEKAR. NEW DELHI: HARPER COLLINS, 2005. PP. 447. RS.395/-. ISBN 81-7223-574-7 - Mukherjee, Panchali (International Journal of Research -GRANTHAALAYAH, 2025)
Amita Kanekar is a Mumbai based writer whose debut novel is A Spoke In The Wheel: A Novel About The Buddha. She teaches Comparative Mythologies and Architectural History at the University of Mumbai, Mumbai, Maharashtra, India. The novel begins with the story of Upali, a monk in the Maheshwar monastery on the banks of the river Narmada. He begins rewriting the life of the Buddha as he sees contradictions in the Suttas. We have a dual narrative structure- alternate chapters are devoted to the story of Upali set in 256 BCE, during the emperor Ashoka’s reign, and the story of the Buddha three hundred years earlier (as retold by Upali). The novel has two parallel plots. It depicts specific moments in history such as the death of Tara because of a slave revolt in Buddha’s time or of Buddha’s charioteer Gopal during the war with the Koliyas or his stay in Benaras that changed Siddarth to Buddha. Upali’s life on the other hand is shown to be affected by the life and teachings of Buddha, by the Kalinga war and by the historical figure of Ashoka that makes him cynical towards the imperial power and the king’s efforts to spread the message of Dhamma. Both Buddha and Upali are typical men of their age who epitomize the processes of change in the society.